Removal of a fish bone in the thyroid gland without the need for thyroid lobectomy. - Arumainathan, U.D.; Lwin, S.; Suan, T.L.; Raman, R. (SAGE Publications, 2000)
We report the first published case of the removal of a migratory fish bone from the thyroid gland that did not necessitate a thyroid lobectomy.